Effect of compound activator on copper slag activity and preparation of filling materials - JIANG Guan-zhao; WU Ai-xiang; WANG Yi-ming; WANG Hong-jiang; LAN Wen-tao; LIU Chao (工程科学学报, 2017)
The preparation of cementitious materials for filling primarily via the alkali-activated method was discussed to recycle copper slags. A mixture of lime, NaOH, and early-strength agent was selected as a composite activator to carry out copper slag activation and filling material-preparation experiments, and the hydration products were analyzed by X-ray diffraction and scanning electron microscopy. The test results show that the effect of different activators on sample strength follows the order lime > early-strength agent > NaOH. The strengths of slag paste samples at 7 and 28 d post-curing reach 1.5 and 3.0 MPa, respectively. The strength of filling materials mixed by copper slag and tailings is 1.0 MPa as the curing ages are 28 d, and the slurry has well fluidity. These values meet the requirements of a suitable filling material. The early hydration products of copper slag mainly include Ca(OH)2 and C-S-H gel. As the curing time increases, the Ca/Si ratio of the C-S-H gel decreases and the structure of the hydration products becomes more compact. After curing for 28 d, the active components in the copper slag are nearly completely reacted.